The Effect of Film Thickness and TiO2 Content on Film Formation from PS/TiO2 Nanocomposites Prepared by Dip‐Coating Method - Sunay, M. Selin; Pekcan, Önder; Ugur, Saziye (Wiley, 2012)
Steady‐state fluorescence (SSF) technique in conjunction with UV‐visible (UVV) technique and atomic force microscope (AFM) was used for studying film formation from TiO2 covered nanosized polystyrene (PS) latex particles (320 nm). The effects of film thickness and TiO2 content on the film formation and structure properties of PS/TiO2 composites were studied. For this purpose, two different sets of PS films with thicknesses of 5 and 20 μm were prepared from pyrene‐(P‐) labeled PS particles and covered with various layers of TiO2 using dip‐coating method. These films were then annealed at elevated temperatures above glass transition temperature (Tg) of PS in the range of 100–280°C. Fluorescence emission intensity, Ip from P and transmitted light intensity, Itr were measured after each annealing step to monitor the stages of film formation. The results showed that film formation from PS latexes occurs on the top surface of PS/TiO2 composites and thus developed independent of TiO2 content for both film sets. But the surface morphology of the films was found to vary with both TiO2 content and film thickness. After removal of PS, thin films provide a quite ordered porous structure while thick films showed nonporous structure.
Keywords: N/A